Post-hemimaxillectomy rehabilitation as a conservative prosthetic design to enhance functionality: A case report - AlTarawneh, Hazem Mofreh Dakhilallah; Buzayan, Muaiyed Mahmoud (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2024)
Background: Oral rehabilitation through prosthetic management after cancer resection is a conservative and effective modality in improving patients’ oral health-related quality of life. However, it is challenging to obtain sufficient retention for hemimaxillectomy and edentulous cases without the use of Osseo-integrated implants. Purpose: This case aims to explain the oral rehabilitation management of post-hemimaxillectomy for edentulous patients using a hollow bulb obturator and long-term soft liner. Case: A 63-year-old female presented to the Universiti Malaya postgraduate dental clinic and complained of a loose obturator during speaking and eating and high resonance during speaking. Seven years ago, she underwent hemimaxillectomy surgery of the left hard palate for the removal of squamous cell carcinoma. Upon examination, she had an edentulous maxillary arch, with a large palatal defect; the lateral border of the defect was lined with a skin graft. The mandibular arch was partially dentate with three teeth remaining (33, 35, 43). Case Management: First, elective root canal treatment of the mandibular canines was done to use them as abutments for a mandibular overdenture. Next, a maxillary hollow bulb obturator and a mandibular overdenture were constructed. Then, after evaluating the airspace on the defect site, the lateral and posterior borders of the obturator were modified to be better utilized for retention. Conclusion: Oral rehabilitation of hemimaxillectomy cases with a hollow bulb obturator without the use of Osseo-integrated implants can be a viable option for improving patients’ mastication, and speech, after assessing the retention factors, including the seal, available undercuts, and occlusion.